Comparing Results of TIMSS and the Hungarian National Assessment of Basic Competencies - Ildikó Balázsi; Ildikó Szepesi (Karolinum Press, 2019)
In our paper, we compared some characteristics of TIMSS 2015 and the National Assessment of Basic Competencies (NABC) 2015. The NABC assesses all students' reading and mathematics performance in Grades 6, 8 and 10. Both studies assessed Hungarian Grade 8 students' mathematics abilities in the spring of 2015. We linked data of the two studies on the student level using Student Measurement IDs. We compared TIMSS and NABC mathematics scales based on the Assessment Framework of the two studies along with the results of students in the two assessments. The comparison of the Frameworks revealed that although the two tests use similar content and cognitive categorizations, there are crucial differences between the two constructs. While the basis of TIMSS's mathematics construct is the common part of mathematics curricula of participating countries, NABC intends to measure mathematical literacy, the ability of students to use their mathematical knowledge and competencies in real life situations. The correlation between the TIMSS and NABC mathematics test results (0.79) also confirms that the two tests measure related, but not identical abilities. To evaluate the representativeness of the TIMSS sample we used school- and class-level weight factors of TIMSS and the student-level weights of NABC combined. The mean performances of the TIMSS sample are only slightly lower than the full NABC cohort's, the effect size of the difference is 0.042 and 0.046 in mathematics and reading respectively. The differences in the standard deviations are somewhat but not considerably larger. The SES-index shows a very good match with no statistically significant differences in the mean and standard deviation of the sample and the full cohort. Our analysis confirms that estimations of population parameters based on TIMSS samples are of a good quality.